Scroll:Sequences and series >> Worked Examples >> saq (4213)


Written Instructions:

For each Multiple Choice Question (MCQ), four options are given. One of them is the correct answer. Make your choice (1,2,3 or 4). Write your answers in the brackets provided..

For each Short Answer Question(SAQ) and Long Answer Question(LAQ), write your answers in the blanks provided.

Leave your answers in the simplest form or correct to two decimal places.



 

1)  

 Write the  each of the following sequences.  (use /)

a1 = -14  ,


an =
 
a -14

n >2 and  Å n£N
 

n+2

 


Answer:_______________




2)  

 Write the  each of the following sequences.  (use /)

a1 = -s1 ,


a=
 
a8-1

n >8 and  Å n£N
 

8+2

 


Answer:_______________




3)  

Write the first five terms of each of the following sequences. 

Given that terms R1 = R2 = 1 and Rn-1 + Rn-2, n = 3,4,5....


Answer:_______________




4)  

 Write the  sequence whose nth term is given by n=3


Cn
 
 n(n+1)(2n+1)
n £ N
 
6



Answer:_______________




5)  

 Write the  each of the following sequences.  (use /)

a1 = -14  ,


an =
 
a -14

n >2 and  Å n£N
 

n+2

 


Answer:_______________




6)  

 Write the  each of the following sequences.  (use /)

a1 = -s1 ,


a=
 
a4-1

n >4 and  Å n£N
 

4+2

 


Answer:_______________




7)  

Write the first five terms of each of the following sequences. 

Given that terms X1 = X2 = 5 and Xn-1 + Xn-2, n = 3,4,5....


Answer:_______________




8)  

 Write the  sequence whose nth term is given by n=2


Cn
 
 n(n+1)(2n+1)
n £ N
 
6



Answer:_______________




9)  

 Write the  each of the following sequences.  (use /)

a1 = -14  ,


an =
 
a -14

n >2 and  Å n£N
 

n+2

 


Answer:_______________




10)  

 Write the  each of the following sequences.  (use /)

a1 = -s1 ,


a=
 
a6-1

n >6 and  Å n£N
 

6+2

 


Answer:_______________




 

1)  

 Write the  each of the following sequences.  (use /)

a1 = -14  ,


an =
 
a -14

n >2 and  Å n£N
 

n+2

 

Answer: 80


SOLUTION 1 :

Given

 a1 = -1 

an an-1
n > 1
 
n+2

 

a= -14
-120
 
3+2 

 



2)  

 Write the  each of the following sequences.  (use /)

a1 = -s1 ,


a=
 
a8-1

n >8 and  Å n£N
 

8+2

 

Answer: -110


SOLUTION 1 :

Given

 a1 = -1 

an an-1
n > 1
 
n+2

 

a=a1
-110
 
8+2 

 



3)  

Write the first five terms of each of the following sequences. 

Given that terms W1 = W2 = 1 and Wn-1 + Wn-2, n = 3,4,5....

Answer: 1,1,2,3,5


SOLUTION 1 :

 Now , W1 = 1, W2 = 1

W3 = W+ W1 = 1 + 1 = 2

W = W3 + W2 = 2 + 1 = 3

W5 = W4 + W3 = 3 + 2 = 5



4)  

 Write the  sequence whose nth term is given by n=3


Cn
 
 n(n+1)(2n+1)
n £ N
 
6


Answer: 14


SOLUTION 1 :

 Here, 


Here  Cn
 
 n(n+1)(2 n+1)
£ N
 
6

 


n = 3,Cn
 
 3(3+1) x (2x3)+1)
=
 
 (3)x(4)x(7)
6 6

 

n = 3
 

 84
=
 
14 
6
 

 



5)  

 Write the  each of the following sequences.  (use /)

a1 = -14  ,


an =
 
a -14

n >2 and  Å n£N
 

n+2

 

Answer: 80


SOLUTION 1 :

Given

 a1 = -1 

an an-1
n > 1
 
n+2

 

a= -14
-120
 
3+2 

 



6)  

 Write the  each of the following sequences.  (use /)

a1 = -s1 ,


a=
 
a4-1

n >4 and  Å n£N
 

4+2

 

Answer: -16


SOLUTION 1 :

Given

 a1 = -1 

an an-1
n > 1
 
n+2

 

a=a1
-16
 
4+2 

 



7)  

Write the first five terms of each of the following sequences. 

Given that terms B1 = B2 = 5 and Bn-1 + Bn-2, n = 3,4,5....

Answer: 5,5,10,15,25


SOLUTION 1 :

 Now , B1 = 5, B2 = 5

B3 = B+ B1 = 5 + 5 = 10

B = B3 + B2 = 10 + 5 = 15

B5 = B4 + B3 = 15 + 10 = 25



8)  

 Write the  sequence whose nth term is given by n=2


Cn
 
 n(n+1)(2n+1)
n £ N
 
6


Answer: 5


SOLUTION 1 :

 Here, 


Here  Cn
 
 n(n+1)(2 n+1)
£ N
 
6

 


n = 2,Cn
 
 2(2+1) x (2x2)+1)
=
 
 (2)x(3)x(5)
6 6

 

n = 2
 

 30
=
 
6
 

 



9)  

 Write the  each of the following sequences.  (use /)

a1 = -14  ,


an =
 
a -14

n >2 and  Å n£N
 

n+2

 

Answer: 80


SOLUTION 1 :

Given

 a1 = -1 

an an-1
n > 1
 
n+2

 

a= -14
-120
 
3+2 

 



10)  

 Write the  each of the following sequences.  (use /)

a1 = -s1 ,


a=
 
a6-1

n >6 and  Å n£N
 

6+2

 

Answer: -18


SOLUTION 1 :

Given

 a1 = -1 

an an-1
n > 1
 
n+2

 

a=a1
-18
 
6+2